2002
DOI: 10.1097/00129689-200210000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience with Laparoscopic Ileal Pouch-Anal Anastomosis for Ulcerative Colitis

Abstract: The purpose of this study was to describe our minimally invasive technique and outline perioperative and medium-term outcomes in patients undergoing laparoscopic ileal pouch-anal anastomosis (LIPAA) for ulcerative colitis. Data were obtained from a prospectively collected database of 13 LIPPA procedures performed for ulcerative colitis between May 1994 and November 2000. Medium-term quality-of-life follow-up was obtained by telephone interview. Eight males and five females had an LIPAA performed, all of whom h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 28 publications
3
27
0
2
Order By: Relevance
“…However, despite development of laparoscopy in colorectal surgery, very few studies to date have reported large experience of laparoscopic IPAA, mainly because IPAA is considered a major surgical procedure. To our knowledge, in the majority of these studies, fewer than 35 patients were included in each [6,[13][14][15][16][17][18][19][20][21]. Furthermore, because of the complexity of the procedure, in these studies IPAA was mainly performed under either laparoscopy-assisted technique or with a handassisted device and not by total laparoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite development of laparoscopy in colorectal surgery, very few studies to date have reported large experience of laparoscopic IPAA, mainly because IPAA is considered a major surgical procedure. To our knowledge, in the majority of these studies, fewer than 35 patients were included in each [6,[13][14][15][16][17][18][19][20][21]. Furthermore, because of the complexity of the procedure, in these studies IPAA was mainly performed under either laparoscopy-assisted technique or with a handassisted device and not by total laparoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have been devoted to the role of laparoscopy in IPAA and most of them have included patients operated by hand-assisted [6,13] or laparoscopicassisted technique [14][15][16][17][18][19][20][21]. Furthermore, all these series have included fewer than 40 patients.…”
mentioning
confidence: 99%
“…The reported benefits include improved cosmesis, reduced pain, earlier return of bowel function, decreased morbidity, decreased hospital stay, improved nutrition, preservation of immune response, and decreased short-and long-term complications. Moreover, functional outcomes and quality-of-life measurements also are comparable between open and laparoscopic techniques [1,2,9].…”
mentioning
confidence: 87%
“…Many groups have demonstrated good results using a laparoscopic approach for proctocolectomies; however most of them make additional incisions, either medial or Pfannenstiel, to dissect the rectum or to resect the specimen [2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%